2004
DOI: 10.1136/bmj.38029.421863.eb
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for chronic headache in primary care: large, pragmatic, randomised trial

Abstract: Objective To determine the effects of a policy of "use acupuncture" on headache, health status, days off sick, and use of resources in patients with chronic headache compared with a policy of "avoid acupuncture." Design Randomised, controlled trial. Setting General practices in England and Wales. Participants 401 patients with chronic headache, predominantly migraine. Interventions Patients were randomly allocated to receive up to 12 acupuncture treatments over three months or to a control intervention offerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
256
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(272 citation statements)
references
References 20 publications
8
256
1
7
Order By: Relevance
“…Firstly, sham acupuncture may have a stronger psychological effect than the dummy pill typically used as placebo control in drug trials. Along with other groups [22][23][24], we have observed that both acupuncture forms are invasive treatments. Invasive treatment techniques are almost always perceived by patients as profoundly meaningful, and such a strong "meaning response" [25] could contribute to symptom reduction [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, sham acupuncture may have a stronger psychological effect than the dummy pill typically used as placebo control in drug trials. Along with other groups [22][23][24], we have observed that both acupuncture forms are invasive treatments. Invasive treatment techniques are almost always perceived by patients as profoundly meaningful, and such a strong "meaning response" [25] could contribute to symptom reduction [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Needles were inserted superficially (1-3 mm) and were not stimulated, so as to avoid De Qi in the sham group. The number (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and type of needles (sterile, singleuse needles, coated, 0.25-0.30 mm thick, 25-40 mm long), and number (10)(11)(12)(13)(14)(15), length (30 min) and frequency (2/week) of treatment sessions were the same in each group. Investigators were instructed to treat patients in each group identically in all ways other than the placement of needles.…”
Section: Interventionsmentioning
confidence: 99%
“…3,4 Headache pain relief has been obtained from needling both acupuncture points and sham points. [3][4][5][6][7][8][9] It is interesting to question, however, whether the sham acupuncture points used were actual acupuncture points in acupuncture traditions other than Traditional Chinese Medicine and whether the neurological input that occurred during the sham acupuncture treatment was sufficient to trigger the central and peripheral changes associated with acupuncture analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…1 These headaches can evolve and become chronic, exacting considerable personal and social economic cost 2 ; they are the most likely headache to lead to analgesic drug overuse. 1,2 Acupuncture has been found to be clinically beneficial for patients with chronic headaches, particularly migraines [3][4][5][6] and tension-type headaches (TTHs). 7,8 Acupuncture has also been suggested to be an effective first-line complementary alternative medicine modality to treat migraines.…”
Section: Introductionmentioning
confidence: 99%
“…Vickers et al 6 , usando escala de escore para cefaléia e questionário de qualidade de vida SF 36, realizaram um estudo prospectivo, randomizado e controlado com 401 pacientes com queixa de cefaléia crônica (maioria enxaqueca), na rede de atenção primária na Inglaterra e no País de Gales. Ele testou a acupuntura (12 sessões em 3 meses) além de medicação contra os cuidados rotineiros (incluindo a medicação consagrada para a cefaléia).…”
Section: Prática Baseada Em Evidênciasunclassified